Orodje za analizo kompleksnosti programov - Podgorelec, Vili (Uporabna informatika (Ljubljana), 1997)
As we try to fulfill the requirements upon quality of the software products wecannot avoid the use of the complexity metric. There is a lot of different metics and also there are hundreds of tools for analyzing the software with some of those metrics. However, since all tools available are concentrated only on some specific programming metrics, for a comprehensive analysis one has to use a lot of different tools. We wanted to derive an environment that would include all of the mostly used metrics, and since we are also developingnew metrics ourselves, we have developed a tool called Software Complexity Analyzer, based besides upon some classical metrics primarily upon new, more general ones.
Keywords: analiza kvalitete; metrika; programska oprema